2012
DOI: 10.1186/ar3890
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association between CD40 and CD40 ligand polymorphisms and systemic sclerosis

Abstract: IntroductionThe aim of the present study was to investigate the possible role of CD40 and CD40 ligand (CD40LG) genes in the susceptibility and phenotype expression of systemic sclerosis (SSc).MethodsIn total, 2,670 SSc patients and 3,245 healthy individuals from four European populations (Spain, Germany, The Netherlands, and Italy) were included in the study. Five single-nucleotide polymorphisms (SNPs) of CD40 (rs1883832, rs4810485, rs1535045) and CD40LG (rs3092952, rs3092920) were genotyped by using a predesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We hypothesize that the lack of response in the number of cells secreting IgM to TCDD is due to a lesser degree of CD40L-mediated activation of the B cells from these individuals as the number of cells secreting IgM was significantly decreased in these donors. Differences in CD40L activation among our cohort of donors may be due to a plethora of reasons including polymorphisms within CD40 receptor gene, previous and present exposures, infections, inflammation, and many other factors of which we are unable to gather information due to the anonymity of blood donation (Blanco-Kelly et al, 2010;Jacobson et al, 2005;Orozco et al, 2010;Raychaudhuri et al, 2008;Teruel et al, 2012). Surprisingly, 2 of the 6 nonresponsive donors were deemed responsive in assaying the concentration of IgM secreted into the media (ie, ELISA).…”
Section: Discussionmentioning
confidence: 94%
“…We hypothesize that the lack of response in the number of cells secreting IgM to TCDD is due to a lesser degree of CD40L-mediated activation of the B cells from these individuals as the number of cells secreting IgM was significantly decreased in these donors. Differences in CD40L activation among our cohort of donors may be due to a plethora of reasons including polymorphisms within CD40 receptor gene, previous and present exposures, infections, inflammation, and many other factors of which we are unable to gather information due to the anonymity of blood donation (Blanco-Kelly et al, 2010;Jacobson et al, 2005;Orozco et al, 2010;Raychaudhuri et al, 2008;Teruel et al, 2012). Surprisingly, 2 of the 6 nonresponsive donors were deemed responsive in assaying the concentration of IgM secreted into the media (ie, ELISA).…”
Section: Discussionmentioning
confidence: 94%
“…To screen for the maximum number of polymorphisms potentially involved in CD40L protein expression or reported to be associated with immune disorders or inflammation32454864, PCR was performed with eleven primer pairs with corresponding annealing temperatures (Table 3, Supplementary Data S1 for PCR protocols). To promote stable heteroduplex formation, PCR products were denatured for 5 min at 96°C, and then gradually cooled at a rate of 0.5°C per 10 sec over 150 cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Buck and colleagues have been found neither significant differences between patients with multiple sclerosis and SNP of the CD40 (C/T21) gene variant (53). In another study it has been demonstrated that CD40 (rs1883832, rs4810485, and rs1535045)/CD154 (rs3092952, and rs3092920) SNPs has not any role in the susceptibility to systemic sclerosis (54). Here we have shown that among CD40/ CD154 gene variants, CD40 rs1883832 is associated with susceptibility to migraine in Iranian population.…”
Section: Discussionmentioning
confidence: 96%